Standardization of Taqwa (Piety) Scale for Muslims: An Exploratory Study - Fauzia Nazam; Akbar Husain; Mubashir Gull (Islamic Guidance and Counseling Journal, 2022)
Taqwa (piety) is a construct in Islamic psychology. It correlates with a large number of behavior such as sustainable capacity building, Islamic leadership, employees’ happiness, and workplace deviance. But the earlier studies have failed to capture the assessment of taqwa from the Qur'anic perspective. In the present study, an attempt is made to standardize a taqwa scale. In the first phase, a pool of 30 items was generated for each of the three domains of the construct (Faith in God, Love for God, and Fear of God), and subject matter experts judge the items’ content for the relevance, clarity, and simplicity on a 4 point Likert rating scale. Item content validity index and interrater reliability of each item were calculated. In the final version, 28 items remained content valid. A total of 229 Muslim students purposively drawn, completed the measure. The mean age of the participants was 22.66 (SD= 1.84). The Taqwa Scale consisted of twelve items with 6 point-Likert rating scale. Exploratory Factor Analysis yielded three factors, namely, faith in God (7 items), love for God (3 items), and fear of God (2 items). Content validity, inter-rater reliability, factorial validity, composite reliability, and construct validity provide strong evidence of the reliability and validity of the taqwa Scale.